INFLUENCE OF CAPITAL STRUCTURE, OWNERSHIP STRUCTURE, FIRM SIZE AND SALES GROWTH AGAINST FINANCIAL DISTRESS (STUDY ON FAMILY COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE YEAR 2018 -2020) - Wahyuningsih, Dwi Warni; Palupi, Endang; Rapini, Titi (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
At the end of 2019, it became intimidation in itself almost all over the world, this began with the shock of the covid 19 virus. The wider the spread of this virus, the more it will have an impact on the economy in various countries as well as Indonesia. With the hampering of the export and import processes, the level of public consumption is getting lower until the implementation of layoffs in several companies. With the background of these conditions, researchers are interested in studying more deeply the company's financial distress. The financial distress itself can be influenced by several factors such as capital structure, ownership structure, company size, and sales growth. The purpose of this study is to determine the effect of capital structure, ownership structure, firm size, and sales growth on financial distress in family companies. The scope of this study is a family company listed on the IDX which is also an object in the study. This study used data on family companies listed on the Indonesia Stock Exchange for the period 2018 to 2020 with the criteria, namely companies with minimum family ownership of 25%. The data used in this study are financial statements obtained from www.idx.co.id.